The process of the construction of the national identities on the polish‐Lithuanian‐Belarusian borderland - Sadowski, Andrzej (Creativity Studies, 2008)
In this article I will at least try to outline the necessary methodological assumptions for the future researches on the national identities of the inhabitants of the Polish ‐ Belarusian ‐ Lithuanian borderland. Then, using the results of the studies of the identities on the Polish ‐ Belarusian borderland, I will attempt to prove the thesis, that in present conditions, the national identity should not be treated as only subjective reflection of someone's national membership, described with the use of a given set of features on the different levels of objectification, but should be understood broader: declaration of the national identity also means taking of the certain position, defining of someone's place and duties within the dynamic and changeable national structure. We can distinguish four types of the collective actors, which shape the national identities on the studied borderland: (1) ethnic minorities (with which certain categories of the citizens identify), (2) national majorities backed by the power of the state in which the representatives of the minorities live, (3) the “foreigner fatherlands” (R. Brubaker) and (4) international organizations which create certain legal regulations and who monitor (control) their realization. In the studies of the national identity of the Polish‐Belarusian‐Lithuanian borderlands some theoretical approaches can be distinguished. There is a need to define, at least for the use in the studies, the concepts of national minority and ethnic minority, and to create a new theoretical category ‐ “the cultural nation”. The national (ethnic) minority can be distinguished in the specific minority situation, most frequently in the context of the other, dominant majority, as the community, which is less significant, subordinated and often discriminated. The notion of national‐ethnic self‐identification should be associated with the resourcefulness of the representatives of a given minority in certain environments.Tautinio tapatumo formavimosi procesas Lenkijos, Lietuvos ir Baltarusijos pasienyjeSantrauka. Bandoma apibrėžti metodologines prielaidas, būtinas Lenkijos, Baltarusijos ir Lietuvos pasienio tautinio tapatumo ateities tyrinėjimams. Remiantis Lenkijos ir Baltarusijos pasienio tapatumų tyrinėjimų rezultatais, bandoma įrodyti, kad mūsų gyvenamuoju laikotarpiu nacionalinio identiteto samprata neturėtų būti traktuojama tik kaip tam tikros tautinės narystės, kuriai būdingi vienokie ar kitokie bruožai, subjektyvių apmąstymų vaisius. Kur kas tiksliau būtų sakyti, kad šiuolaikinis tautinio tapatumo konceptas kaip toks reiškia tam tikros vietos ir tam tikrų pareigų aiškiai apibrėžtą junginį dinamiškoje ir sparčiai kintančioje nūdienėje nacionalinėje struktūroje. Galima išskirti keturias grupes, apibrėžiančias tautinį tapatumą pasienio ruožuose: 1) etninės mažumos; 2) tautinė dauguma; 3) „svetimšalių tėvynė“ (R. Brubakeris); 4) tarptautinės organizacijos. Būtina apibrėžti tautinės ir etninės mažumų sąvokas bei įtvirtinti naują ją teorinę „kultūrinės tautos“ kategoriją. Tautinių mažumų situacija visada yra specifi nio pobūdžio, nes jos yra neišvengiamai priklausomos ir diskriminuojamos dominuojančios daugumos. Todėl tautinės-etninės saviidentifi kacijos samprata, pasak šio straipsnio autoriaus, negali būti atsieta nuo tam tikros tautinės mažumos atstovų išradingumo.Reikšminiai žodžiai: tautinis tapatumas, tautinė (etninė) mažuma, „kultūrinė tauta“, pasienio ruožas.First Published Online: 14 Oct 2010